Kalle Päätalo tutkijoiden silmin - Saviniemi, Maija (Tietolipas, 2022)
The Finnish novelist Kaarlo (Kalle) Alvar Päätalo's (1919-2000) main work, the Iijoki series, consists of 26 novels (comprising ca. 17 000 pages) and was written in 1971-1998. In this book the text corpus in Kielipankki concerning Päätalo's works is introduced to the readers, as well as the possibilities of digital text mining. This book includes scientific articles concerning the works of Kalle Päätalo. It also gives ideas for the research that can be carried out in the future. The authors of this book are researchers in the fields of history, linguistics and literature, respectively. The research results presented in this book speak for the fact that the Iijoki series is a significant source material for future research, for example from the point of view of oral history, language variation, metalanguage, swearing and the reader's reception. The possibilities for future research seem to be quite plentiful.